2018
DOI: 10.1002/leap.1188
|View full text |Cite
|
Sign up to set email alerts
|

Editorial challenges in a small scientific community: Study of Croatian editors

Abstract: This article presents results from a study of 74 Social Science Croatian journal editors that asked about challenges encountered during their work, with a special focus on peer review processes. The study used an online questionnaire with 19 questions. The findings confirmed many logistics challenges and peer review-related problems associated mostly with substandard work of the reviewers; author misconduct, especially plagiarism; and multiple submission of articles. The findings show similar problems to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…Specifically, we hypothesize that non-Western academics might have alternative views on academic misconduct. Previous studies of the academic periphery have revealed that the level of plagiarism in academia is higher when compared with Western countries (Davis, 2003;Hodges et al, 2017;Lewellyn et al, 2017;Thomas and Bruin, 2015;Vrana, 2018). These findings confirm Clark's (1986) statement that an attachment to a global standard without borders is less evident in non-European and non-North American contexts.…”
Section: Introductionsupporting
confidence: 81%
“…Specifically, we hypothesize that non-Western academics might have alternative views on academic misconduct. Previous studies of the academic periphery have revealed that the level of plagiarism in academia is higher when compared with Western countries (Davis, 2003;Hodges et al, 2017;Lewellyn et al, 2017;Thomas and Bruin, 2015;Vrana, 2018). These findings confirm Clark's (1986) statement that an attachment to a global standard without borders is less evident in non-European and non-North American contexts.…”
Section: Introductionsupporting
confidence: 81%
“…(США), В. Бейкер (США), С. Хейнс (США) у своїх наукових дослідженнях розглядають можливості і вплив рецензентів на удосконалення процесу експертизи [5]. Внесок редакторів наукових видань у просуванні та вдосконаленні своїх журналів, проблеми, які вони повинні вирішувати представлені у дослідженнях М. Марушич, А. Марушич (Хорватія) [6], Р. Врано (Хорватія) [7]. Г. МакДоуел (США), Дж.…”
Section: The Electronic Scientific Professional Edition "Information unclassified
“…When attempting to estimate the scale of plagiarism, most research looks at post‐publication problems, but these do not consider plagiarism in article submissions, which may not make it through to publication. In his 2017 survey, Vrana () identified plagiarized submissions as an item of major concern amongst Croatian editors. The small‐scale survey demonstrated that it was the second largest problem that the editors experienced.…”
Section: Introductionmentioning
confidence: 99%